Supersaturable organic-inorganic hybrid matrix based on well-ordered mesoporous silica to improve the bioavailability of water insoluble drugs. (1st January 2020) - Wu, Qiaoli; Feng, Disang; Huang, Zhengwei; Chen, Minglong; Yang, Dan; Pan, Xin; Lu, Chao; Quan, Guilan; Wu, Chuanbin
Abstract: Mesoporous silica with uniform 2-D hexagonal pores has been newly employed as facile reservoir to impove the dissolution rate of water insoluble drugs. However, rapid drug release from mesoporous silica is usually accompanied by the generation of supersaturated solution, which leads to the drug precipitation and compromised absorption. To address this issue, a supersaturated ternary hybrid system was constructed in this study by utilizing inorganic mesoporous silica and organic precipitation inhibitor. Vinylprrolidone-vinylacetate copolymer (PVP VA64) with similar solubility parameter to model drug fenofibrate (FNB) was expected to well inhibit the precipitation. Mesoporous silica Santa Barbara amorphous-15 (SBA-15) was synthesized in acidic media and hybrid matrix was produced by hot melt extrusion technique. The results of in vitro supersaturation dissolution test obviously revealed that the presence of PVP VA64 could effectively sustain a higher apparent concentration. PVP VA64 was suggested to simultaneously reduce the rate of nucleation and crystal growth and subsequently maintain a metastable supersaturated state. The absorption of FNB delivered by the organic-inorganic hybrid matrix was remarkably enhanced in beagle dogs, and its AUC value was 1.92-fold higher than that of FNB loaded mesoporous silica without PVP VA 64. In conclusion, the supersaturated organic-inorganic hybrid matrix can serve as a modular strategy to enhance the oral availability of water insoluble drugs.